PENERAPAN AHP DAN TOPSIS UNTUK PENILAIAN KELAYAKAN KREDIT PADA BPR CENTRADANA KAPUAS PONTIANAK - Irawan Wingdes; Tri Widayanti (Universitas Raharja, 2017)
Financing for business or consumption is one of the main purpose of a bank. BPR is mini part of Indonesian banking system that functions like conventional banks with limited or smaller role. BPR also finances for car loans. In practice, when administrative assessments for car loan applications are not met, subjective assessment is needed to further assess car loan applications. The purpose of this study is to develop decision support for the latter problem. This study employs AHP and TOPSIS as decision support method. 5C’s are used for assesment which results in highest preference in Character (0.36), followed by Capacity (0.28), Capital (0.19), Collateral (0.14), Condition (0.04). Fifteen sub criterias are also developed to further assess the loan and TOPSIS is used for alternative selection. The result of this study proves AHP and TOPSIS are reliable for supporting multi criteria decision making, especially in assessing and approving car credit loan at BPR Centradana Kapuas Pontianak.